Respuesta :

Answer:

C

Step-by-step explanation:

Using the rule of radicals

[tex]\sqrt{a}[/tex] × [tex]\sqrt{b}[/tex] ⇔ [tex]\sqrt{ab}[/tex]

Simplifying each radical before combining them.

[tex]\sqrt{45t}[/tex]

= [tex]\sqrt{9(5t)}[/tex]

= [tex]\sqrt{9}[/tex] × [tex]\sqrt{5t}[/tex] = 3[tex]\sqrt{5t}[/tex]

-----------------------------------------------------------------------------

[tex]\sqrt{125t}[/tex]

= [tex]\sqrt{25(5t)}[/tex]

= [tex]\sqrt{25}[/tex] × [tex]\sqrt{5t}[/tex] = 5[tex]\sqrt{5t}[/tex]

---------------------------------------------------------------------------

Hence

2(3[tex]\sqrt{5t}[/tex]) - 3(5[tex]\sqrt{5t}[/tex]

= 6[tex]\sqrt{5t}[/tex] - 15[tex]\sqrt{5t}[/tex]

= - 9[tex]\sqrt{5t}[/tex] → C

ACCESS MORE